Population Ecology and Regeneration Status of Buxus wallichiana (Himalayan Box Tree) in Rajouri-Poonch Districts, Jammu and Kashmir, India: Honing Red List of Plants - Ahmed, Khurshid; Pant, Shreekar; Rinchen, Tsewang (Indian Forester, 2015)
The Himalayan Box tree (Buxus wallichiana) is valuable and vulnerable tree associated with Rajouri-Poonch culture. Due to its manifold uses and utilization its risk of extinction has increased. The species does not regenerate well from seed that is another risk factor. The objective of this research was to investigate the population ecology of the data deficient tree species as a foundation for its conservation. Five forest communities in the Rajouri-Poonch district were sampled. The abundance of the species, impacts of harvesting and its current regeneration patterns indicated that it may soon be extirpated from the study area. A plan for conserving the remaining sub-populations is presented. It could provide a template for conservation in other locations where the species is at risk.